Wilprafen in treatment of the chronic urogenital chlamydiosis - V. A. Molochkov; A. E. Gushchin; E. V. Balyura (Сеченовский вестник, 2013)
The treatment of 40 patients with chronic urogenital chlamydiosis with Wilprafenom (500 mg 2 times a day during 21 days) in combination with the drug interleukin-beta, systemic enzyme therapy, physiotherapy and adequate local treatment was made. The clinical cure was achieved in 36 (90%), an improvement — in 4 (10%) cases, bacterial eradication occurred in 38 (95%) cases. The results indicate the high efficiency of treatment.